An Analysis of Inglo Restaurant's Strategies in Retaining Consumers in the Covid-19 Pandemic Era - Ramadhan, Ghifary (Gastronomy Tourism Journal, 2021)
Strategy is an important thing that can influence the sustainability of the restaurant. All policies to be realized, always go through a strategic process. This research was conducted at the Inglo restaurant with the aim of knowing the strategies used by the Inglo restaurant to defend consumers during the Pandemic era. The method used in this research is descriptive qualitative using purposive sampling technique through observation, interviews and documentation. Seeing that the pandemic era is still a threat, the strategies used by the Inglo restaurant can still increase, decrease and change. The results of this study show that the Inglo restaurant has three main strategies, namely implementing health protocols, providing services through online media and reducing costs. This strategy was successful in maintaining the sustainability of the Inglo restaurant in its business and the strategy implemented was able to maintain consumers in terms of service, good image of the Inglo restaurant and consumer satisfaction in the pandemic era.